Perancangan Ergonomic Automix-Liquid Soap dan Kelayakan Investasi Guna Meningkatkan Kapasitas Produksi di PT. SKI - Aulia, Dian Rahma; Satoto, Handy Febri (Fakultas Teknik UMRI, 2025)
PT. SKI produces GoClink liquid soap but faces challenges in detergent production, especially during mixing, which uses a semi-automatic tool. Mixing and stirring take about 43 minutes for 80 liters per day, done by 2 operators with poor ergonomic posture (REBA score 10). This study designs an automatic mixer (Automix-Liquid Soap) based on anthropometry and ergonomics to boost capacity, speed up production, and reduce operator workload. Methods include field observation, Stopwatch Time Study, REBA evaluation, design based on anthropometric data from 5 workers, and investment feasibility analysis using Net Present Value (NPV). Results show mixing time improved by 71.2%, cutting 184.54 seconds (from 259.14 to 74.60 seconds), and stirring time improved by 71.3%, reducing 1,667.34 seconds (from 2,338.2 to 670.86 seconds). Capacity rose to 180 liters, REBA score improved to 2, and labor efficiency increased by 50%. An investment of Rp10,589,625 is financially viable with a positive NPV of Rp20,372,845.